MODERN TREATMENT OF ACUTE RHINOSINOCYTES - Bobokulova D.F. (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation: many drugs available in the pharmaceutical market set the task of otolaryngologists to choose rational and safe methods of treating patients with diseases of  the  nose  and  paranasal  sinuses.  Herbal  preparations  have  such  non-existent properties as a comprehensive effect on the body with low toxicity and high efficiency. This allows when using herbal preparations not only  for treatment, but also for the Prevention of diseases. The essential oil contained in medicinal turmeric prevents the growth of bacteria and has an immunomodulatory property.